2020
DOI: 10.1016/j.ijid.2020.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii SAG2 type III in an atypical presentation of ocular toxoplasmosis in Indonesia

Abstract: This study aimed to perform genotyping of Toxoplasma gondii strain or variant causing atypical toxoplasmic uveitis in Indonesian patients. Methods: Ocular fluid samples originating from 46 uveitis patients with non-specific ocular manifestations were analysed for Toxoplasma infection by PCR of the B1 locus. The clonal type was determined by amplification, sequencing and phylogenetic analysis of SAG2 and GRA6 loci in B1-positive samples. Clinical data were obtained from the medical records. Results: Pan uveitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Among cancer patients in China, Wang et al [ 18 ] revealed a 3.55% positivity rate of T. gondii by nested PCR at the GRA6 locus. On the other hand, no positive result was obtained from amplification of the GRA6 gene in patients with ocular toxoplasmosis in Indonesia [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among cancer patients in China, Wang et al [ 18 ] revealed a 3.55% positivity rate of T. gondii by nested PCR at the GRA6 locus. On the other hand, no positive result was obtained from amplification of the GRA6 gene in patients with ocular toxoplasmosis in Indonesia [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Genotyping of Toxoplasma from ocular fluid samples in patients with uveitis in Indonesia by analysis of SAG2 and GRA6 loci showed that all samples were of type III allele [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Indonesian population, toxoplasmosis should be considered as a cause of atypical posterior uveitis or panuveitis. 18 However, the timing of PCR analysis appeared to significantly affect the positivity of T. gondii PCR. De Groot-Mijnes et al observed that the positivity of T. gondii declined if samples were collected and analyzed at four weeks after onset.…”
Section: Discussionmentioning
confidence: 99%
“…Toxoplasmosis in humans can cause miscarriage, chorioretinitis and uveitis, encephalitis and cerebral calcification, hydrocephalus, and birth defects (Montoya, 2002;Capobiango et al, 2016). Cases of toxoplasmosis in Indonesia are reported to exceed 60% in people of the children bearing-age (Terazawa et al, 2003) and 19% in uveitis cases (Kurniawan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%